2006
DOI: 10.1021/jo052631n
|View full text |Cite
|
Sign up to set email alerts
|

NMR Method for the Determination of Solute Hydrogen Bond Acidity

Abstract: It is shown that the difference in the 1H NMR chemical shift of a protic hydrogen in DMSO and CDCl3 solvents is directly related to the overall, or summation, hydrogen bond acidity for a wide range of solutes. This provides a new and direct method of measuring the hydrogen bond acidity. For 54 compounds, the observed shifts for 72 protic hydrogens could be correlated to the Abraham solute hydrogen bond acidity parameter, A, with a correlation coefficient squared, R2, of 0.938 and a standard deviation, SD, of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
87
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 45 publications
6
87
0
Order By: Relevance
“…We denote the hydrogen atom that is involved in an intraHB as H b and the hydrogen atom that does not take part in an intraHB as H a . Table 3 presents values of Δδ(NH) and the deduced A NMR values for a number of nitrogen compounds, 16,[19][20][21]23,25 including two agrochemicals, fipronil and imidacloprid ( Figure 2). 11 Shalaeva et al 1 also determined Δδ(NH) for several of the compounds they had studied using the Δ(log P) oct−tol method, but they did not make any use of the Δδ values.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We denote the hydrogen atom that is involved in an intraHB as H b and the hydrogen atom that does not take part in an intraHB as H a . Table 3 presents values of Δδ(NH) and the deduced A NMR values for a number of nitrogen compounds, 16,[19][20][21]23,25 including two agrochemicals, fipronil and imidacloprid ( Figure 2). 11 Shalaeva et al 1 also determined Δδ(NH) for several of the compounds they had studied using the Δ(log P) oct−tol method, but they did not make any use of the Δδ values.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, E can be obtained either from a calculated refractive index at 293 K [12], or even better as a calculated value using the ACD software [13] and V can be calculated from structure [7]. In the present case, we are fortunate that Whaley et al [14] have determined A-values for hydroxyflavones using an NMR method [15], and we can use this data to assign A = 1.92 for quercetin. Then the outstanding descriptors of quercetin to calculate are reduced to S, B, L, log Kw and log Cw.…”
Section: Methodsmentioning
confidence: 98%
“…One of the key descriptors is the overall, or effective, hydrogen bond acidity, A, in which we were particularly interested, especially as we have recently developed a new method for the experimental determination of this parameter. 3 In this work, we showed that the difference (Δδ) in the As we have pointed out, 1 the overall or effective hydrogen bond acidity, A, is the important type of acidity when considering processes in which a solute is in dilute solution and surrounded by solvent molecules, or is present in the gas phase as an isolated molecule. A related acidity is the 1:1 hydrogen bond acidity, α 2 H , in which a solute complexes with a hydrogen bond base in an inert solvent such as tetrachloromethane.…”
Section: Introductionmentioning
confidence: 92%
“…A related acidity is the 1:1 hydrogen bond acidity, α 2 H , in which a solute complexes with a hydrogen bond base in an inert solvent such as tetrachloromethane. 1,4 The defining equations for α 2 H are eqn (1), 4 where K is the 1:1 complexation constant for an acid against a reference base B, eqn (2) in which log K is put on a general scale of hydrogen bond acidity K A H , and finally eqn (3) is known, the general equation, eqn (4), 7 can be used to estimate the 1:1 complexation constant of the oximes or of the hydroxylamine with any base for which the 1:1 hydrogen bond basicity β 2 H has been determined. [8][9][10][11] Log K = (7.354* α 2…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation